Outside the Classroom: The Language of English and its Impact on International Student Mental Wellbeing in Australia - Gomes, Catherine (Journal of International Students, 2020)
International students from culturally and linguistically diverse countries travel to Australia because of the opportunity to study courses in the English language with some coming to this country just to study the language itself. Such desires moreover create students to engage in creative strategies to improve their language skills. This paper, however, suggests that the desire to be skilled in English through immersion in an English-speaking country like Australia creates challenges to the mental wellbeing of international students. Reporting on interview data with 47 international students of Asian descent in the Australian city of Melbourne, this paper reveals these challenges to include lived and perceived notions of self and belonging, as well as loneliness.